Detached Anterior Horn of the Medial Meniscus Mimicking a Parameniscal Cyst - Shoji Fukuta; Takahiko Tsutsui; Tetsuya Matsuura; Naoto Suzue; Daisuke Hamada; Tomohiro Goto; Koichi Sairyo (Case Reports in Orthopedics)
We report a case of a detached anterior horn of the medial meniscus with anterior knee pain. Preoperative magnetic resonance images of the knee were initially interpreted as a parameniscal cyst. Arthroscopic examination revealed subluxation of the anterior horn of the medial meniscus due to detachment from its anterior tibial insertion. Arthroscopic fixation with a suture anchor was successful and the cystic lesion was no longer visible on postoperative images.